1969
DOI: 10.1530/jrf.0.0200419
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Isolation of a Sperm-Coating Antigen From Rabbit Seminal Plasma With Capacity to Block Fertilization

Abstract: Summary. The relationship between the sperm-coating antigens of rabbit seminal plasma and the phenomenon of decapacitation was studied using agar-gel diffusion, immuno-electrophoresis, chromatography on Sephadex G-200, and polyacrylamide vertical gel electrophoresis.Interpretation of data obtained with these techniques led to the conclusion that a sperm-coating antigen of seminal plasma origin possessed biological activity for blocking fertilization. The sperm-coating antigen was a glycoprotein of approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

1971
1971
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Since Bedford and Chang (1962) first suggested that a mucoprotein may be involved in decapacitation, several reports have supported this contention (Hunter and Nornes, 1969;Reyes et al, 1975;Eng and Oliphant, 1978;Thomas et al, 1984). Immunoelectrophoresis using antiserum against whole seminal plasma indicated that one antigen was readily removed from seminal plasma by 4 hr of ultracentrifugation (Hunter and Nornes, 1969).…”
Section: Stabilization Of the Acrosome And Consequential Sperm Decapamentioning
confidence: 99%
See 1 more Smart Citation
“…Since Bedford and Chang (1962) first suggested that a mucoprotein may be involved in decapacitation, several reports have supported this contention (Hunter and Nornes, 1969;Reyes et al, 1975;Eng and Oliphant, 1978;Thomas et al, 1984). Immunoelectrophoresis using antiserum against whole seminal plasma indicated that one antigen was readily removed from seminal plasma by 4 hr of ultracentrifugation (Hunter and Nornes, 1969).…”
Section: Stabilization Of the Acrosome And Consequential Sperm Decapamentioning
confidence: 99%
“…Immunoelectrophoresis using antiserum against whole seminal plasma indicated that one antigen was readily removed from seminal plasma by 4 hr of ultracentrifugation (Hunter and Nornes, 1969). Since it was well established that such treatment removed the decapacitation activity (Bedford and Chang, 1962;Weinman and Williams, 19641, Hunter and Nornes concluded that this glycoprotein must have decapacitation activity.…”
Section: Stabilization Of the Acrosome And Consequential Sperm Decapamentioning
confidence: 99%
“…Isolation of the inhibitor of fertilization in rabbit seminal plasma has recently been reported by other workers (13). These authors failed, however, to give data directly concerning inhibitory activity in the purified fraction; moreover, they attribute to it a molecular weight of 170,000.…”
Section: Resultsmentioning
confidence: 95%
“…In addition to motility and morphology of the spermatozoa, factors such as biochemical characteristics of sperm cells and seminal plasma, uterine contractility, and the micro-environment of the female reproductive tract might be essential components for successful fertilization to take place. This is supported by studies on both horses and other species, suggesting that the integrity of the macromolecules of the sperm membrane is an important component of sperm longevity in sows (Pavelko and Crabo 1976), that uterine contractility in response to semen may be associated with sperm transport in the mare (Katila et al 2000), that sperm transport is affected by prostaglandin in ram semen (Gustavsson et al 1977), and that membrane biochemistry is important for sperm capacitation, acrosome reaction and the final steps of fertilization (Hunter and Nornes 1969). All these factors may affect transport and survival of viable spermatozoa, and elimination of non-viable and excess spermatozoa from the mare's reproductive tract.…”
Section: Introductionmentioning
confidence: 99%